Characteristics of GNSS Total Electron Content Enhancements Over the Midlatitudes During a Geomagnetic Storm on 7 and 8 November 2004. Issue 12 (4th December 2019) - Sori, T.; Shinbori, A.; Otsuka, Y.; Tsugawa, T.; Nishioka, M.
Abstract: The characteristics of global electron density variations in the ionosphere during a geomagnetic storm on 7 and 8 November 2004 were investigated using total electron content (TEC) obtained from the global navigation satellite system (GNSS). The regions of enhanced TEC over North America, Europe, and Japan first appeared in the middle‐latitude regions. The TEC enhancements over North America showed a rapid longitudinal expansion and reached a wide longitudinal extent during the initial and main phases of the geomagnetic storm. TEC enhancements were simultaneously observed in both North America and Japan at 05:00 UT on 8 November. Observation data from the Defense Meteorological Satellite Program showed a slight enhancement of electron density at 850 km below the equatorward boundary of the middle‐latitude trough (45–48°N in geomagnetic latitude) over the Pacific Ocean. This electron density variation may correspond to the TEC enhancements observed in both Japan and North America. These results imply that an enhanced TEC region existed between North America and Japan. The TEC enhancement in Japan appeared with a magnetic conjugacy in the Southern Hemisphere, indicating one of the characteristics of storm‐enhanced density (SED). Moreover, TEC enhancements simultaneously appeared from Japan to central Asia at 11:00 UT on 8 November, corresponding to the early recovery phase of the geomagnetic storm. From the above results, it is suggested that SED phenomena can be simultaneously generated over a wide longitudinal width ( 100°). The longitudinal extent of this SED event is 2.5–5.0 times longer than those reported by previous studies. Key Points: TEC enhancements first appeared in the middle‐latitude regions associated with the geomagnetic storm The TEC enhancement observed in Japan appeared with a magnetic conjugacy in the Southern Hemisphere TEC enhancements in the afternoon to night sectors were simultaneously observed within a wide longitudinal width ( 100°)